2021
DOI: 10.1002/lary.29849
|View full text |Cite
|
Sign up to set email alerts
|

Readability of Commonly Used Patient‐Reported Outcome Measures in Laryngology

Abstract: Objectives Patient‐reported outcome measures (PROMs) are used to evaluate patients' symptoms and clinical improvement after an intervention. Advocacy efforts and increased provider awareness regarding health literacy have helped to improve the readability of PROMs. Recent studies in otolaryngology in rhinology, pediatric otolaryngology, and head and neck reported PROM readability scores above the sixth‐grade level. However, there is limited data regarding the readability of laryngology PROMs. Thus, this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
1
1
Order By: Relevance
“…PROMs are commonly utilized in laryngology to describe the impact of dyspnea, dysphonia, and dysphagia on patients' functionality and quality of life. 15 Patients in the current study reported an improvement in DI, EAT-10, and VHI-10 scores post-operatively across all cohorts; however, none of these changes reached the level of statistical significance. Whether or not these changes represent a clinically meaningful difference requires further study.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…PROMs are commonly utilized in laryngology to describe the impact of dyspnea, dysphonia, and dysphagia on patients' functionality and quality of life. 15 Patients in the current study reported an improvement in DI, EAT-10, and VHI-10 scores post-operatively across all cohorts; however, none of these changes reached the level of statistical significance. Whether or not these changes represent a clinically meaningful difference requires further study.…”
Section: Discussioncontrasting
confidence: 54%
“…Airway stenosis may cause acute or chronic upper airway obstruction and significantly impact a patient's quality of life. PROMs are commonly utilized in laryngology to describe the impact of dyspnea, dysphonia, and dysphagia on patients' functionality and quality of life 15 . Patients in the current study reported an improvement in DI, EAT‐10, and VHI‐10 scores post‐operatively across all cohorts; however, none of these changes reached the level of statistical significance.…”
Section: Discussionmentioning
confidence: 58%